Ovarian localization of 11b-hydroxysteroid dehydrogenase (11bHSD): effects of ACTH stimulation and its relationship with bovine cystic ovarian disease - Amweg, Ayelen Noelia (2013)
Cystic ovarian disease (COD) is an important cause of infertility in cattle, and ACTH has been involved in regulatory mechanisms related to ovarian function associated with ovulation, steroidogenesis, and luteal function. Here, we examined the localization of 11β-hydroxysteroid dehydrogenase type 1 (11βHSD1) and 11βHSD2 proteins in the ovary of healthy cows and animals with spontaneous and ACTH-induced COD and the in vitro response of the follicular wall exposed to ACTH. After stimulation by ACTH, we documented changes in 11βHSD expression and cortisol secretion by the follicular wall of large antral and follicular cysts. Follicular cysts showed a higher constitutive expression of both enzymes, whereas ACTH induced an increase in 11βHSD1 in tertiary follicles and follicular cysts and a decrease in 11βHSD2 in follicular cysts. Moderate expression of 11βHSD1 was observed by immunohistochemistry in granulosa of control animals, with an increase (P < 0.05) from primary to secondary, tertiary, and atretic follicles. The level of immunostaining in theca interna was lower than that in granulosa. The expression of 11βHSD2 was lower in the granulosa of primary follicles than in that of secondary, tertiary, and atretic follicles and was lower in the theca interna than in the granulosa. In ACTH-induced and spontaneously occurring follicular cysts, differences from controls were observed only in the expression of 11βHSD1 in the granulosa, being higher (P < 0.05) than in tertiary follicles. These findings indicate that follicular cysts may be exposed to high local concentrations of active glucocorticoids and indicate a local role for cortisol in COD pathogenesis and in regulatory mechanisms of ovarian function.